A influência dos princípios éticos na atuação profissional do gestor: um estudo de caso - Almeida, Milena Bahiense (2013)
In a time when the world is experiencing deep transformations to talk about ethic in a general sense and ethic that starts from the managerial point of view which is the organizational conductor, it is highly important by the proposed reflection of the values in a globalized era characterized by the competitiveness marketing in the field of administration. The general objective of this study is to investigate if the ethical profile of the manager have influence in the environment where is inserted. According to the mentioned objectives this study is defined as a qualitative investigation such as exploratory seeking to consider a better understanding of the problem in order to make it more precise. For the reason that the ethical analysis be restricted in the example of a manager in a company grou located in a state of Bahia, this is a case study. Therefore, the proposed investigative methodology refers to the qualitative study with the support of the semi- structure interview of the manager speaking about the influence of the principles of the Care Ethic in the professional dealings of the modern manager which the investigative instrument of collected data went for Bardin analisis of the content in the light of the Theory of Social Representations. It was identified in this study the importance of the profile and ethic role of the manager and his influence in the internal and external organizational environment since that the relevant entities in the existence of the company tends to look to the managers as role models. The study also presents the challenge of the modern manager to overcome the many situations imposed by the changes in the trends of the globalized world considering the responsibilities of the socio-environment which is originated by the ethical standard.